From Anti-Politician Technocratism to Anti-Immigrant Nativism? - Naxera, Vladimír (Communist and post-communist studies, 2025)
This article focusing on the communications of former Czech PM Andrej Babiš is a contribution to the debate on the transformation of the communications of populist actors. Using a content analysis of all Facebook communication in the profiles of Babiš and his ANO movement in the pre-election periods between 2013 and 2023, the text reveals a gradual transformation of communication. While the level of populism in communication remained relatively high throughout the decade (with a notable peak in the run-up to the 2017 parliamentary elections, after four years of government engagement), other (ideological) features accompanying populism transformed significantly. The initial technocratic, expert, and managerial rhetoric putting in contrast “bad ideological/party politicians” and “good experts and managers” was pragmatically abandoned over time and replaced by a nativist rhetoric placing in contrast “good natives” and “bad incomers,” that is, immigrants (and not immediately after the outbreak of the so-called migration crisis). In this respect, the transformation of the communication of ANO and Babiš differs from the communication of a large part of other dominant Central European populist actors.